2016
DOI: 10.1080/10942912.2016.1163577
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and malachite green residues in farmed rainbow trout (Oncorhynchus mykiss) from the Iranian markets: A risk assessment

Abstract: Antibiotic and malachite green residues in farmed rainbow trout muscles were determined by high-performance liquid chromatography for a food risk assessment. The surveillance was carried out on total of 120 rainbow trout fillets, all fishes were randomly sampled from 20 fish markets of Iran. All antibiotics were detected in the range of 0.42-1.20 μg/g for Oxytetracycline, 0.02-0.34 μg/g for Enrofloxacin, 0.21-2.61 μg/g for Florfenicol, and finally 0.02-0.89 μg/g for Malachite green. Our results showed that 99 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Although these drugs are highly effective against fish diseases caused by fungal and bacterial infections in aquatic environments, they are banned in aquaculture practices because they may pose health risks and adverse environmental impact [13]. However, these prohibited drugs are still frequently used in many places around the world, due to their low cost and effectiveness in the control of fish diseases [14,15,16]. Ultra-sensitive chromatographic methods, such as liquid chromatography-tandem mass spectrometry (LC-MS/MS) with a limit of detection equal to or below 1 ppb are required to analyze these zero-tolerance chemicals in fish and fish products [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although these drugs are highly effective against fish diseases caused by fungal and bacterial infections in aquatic environments, they are banned in aquaculture practices because they may pose health risks and adverse environmental impact [13]. However, these prohibited drugs are still frequently used in many places around the world, due to their low cost and effectiveness in the control of fish diseases [14,15,16]. Ultra-sensitive chromatographic methods, such as liquid chromatography-tandem mass spectrometry (LC-MS/MS) with a limit of detection equal to or below 1 ppb are required to analyze these zero-tolerance chemicals in fish and fish products [17].…”
Section: Introductionmentioning
confidence: 99%
“…[24] In a previous survey conducted in Iran, 70 out of 144 rainbow trout samples (48.6%) contained residues of MG, ranging between 0.3 and 146.1 µg/kg. [27] In a recent study performed in Iran, it was found that 70 out of 120 samples (58.4%) obtained from fish markets contained detectable residues of MG. [6] In order to determine the residues of MG in farmed fish samples in the United Kingdom, monitoring and inspection programs were continuously performed from 2001 to 2011. [28] In 2001, 2002, and 2003, 16.1%, 9.9%, and 4.2% of tested farmed salmon and trout samples contained MG and LMG residues, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] It is very effective for the treatment of external parasites and protozoan, e.g., Ichthyophthirius, Chilodonella, and Trichodina in aquaculture. [6][7][8] MG causes damage to liver, spleen, and kidney, decreases food intake, produces teratogenic and carcinogenic effects, and is highly cytotoxic to mammalian cells. During waterborne exposure, MG is easily absorbed into fish tissues and transformed to the reduced, colourless compound, leucomalachite green (LMG), which is lipophilic and remains in fatty tissues for extended periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are extensively used to prevent or treat bacterial infections in humans, animals and plants (Balarak et al 2017 ). Antibiotics use in modern aquacultures in diverse areas including Iran in large scale to prevent or treat the infectious diseases in fishes (Adel et al 2017 ). The WHO has declared that widespread application of antibiotic in the aquacultures may cause risks for the consumer contributing to the antibacterial resistance in human and veterinary medicine due to the accumulation of their residues in edible tissues of fish (Adel et al 2017 ; Conti et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics use in modern aquacultures in diverse areas including Iran in large scale to prevent or treat the infectious diseases in fishes (Adel et al 2017 ). The WHO has declared that widespread application of antibiotic in the aquacultures may cause risks for the consumer contributing to the antibacterial resistance in human and veterinary medicine due to the accumulation of their residues in edible tissues of fish (Adel et al 2017 ; Conti et al 2015 ). Also, antibiotics can release into the surrounding waters during treatment of fish stocks and cause some environmental problems (Adel et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%